Integrasi Teknologi dalam Manajemen Pendidikan: Peluang dan Tantangan - Hesti Kusumaningrum; Aidah Mutma Innah Nst; Fathia Kharisma Nur Fayza; Ananda Citra Isfayanti (Al-Gafari : Manajemen dan Pendidikan, 2024)
Technology integration in education management has become a crucial aspect in efforts to improve the quality of education in the digital era. This article examines the opportunities and challenges faced in the application of technology in education management. The main opportunities that arise include increasing administrative efficiency, easier access to information, and developing more interactive and adaptive technology-based learning. On the other hand, the challenges faced include gaps in access to technology, lack of training for educators, and organizational cultural barriers in technology adoption. This study aims to provide insights for education stakeholders in formulating effective strategies to utilize technology, while addressing existing challenges. With the right approach, technology integration can be a catalyst for improving the quality of education that is more inclusive and globally competitive.